Sjögren's Syndrome: Current Insights into Pathogenesis, Diagnosis and Treatment - Lompart, Albert; Kosarewicz, Albert; Krysiak, Patrycja; Woźniak, Łukasz; Wabiszczewicz, Michał (Quality in Sport, 2025)
Sjögren’s syndrome is a chronic autoimmune disease mainly targeting exocrine glands with resultant dry eyes and mouth symptoms, plus systemic manifestations of fatigue, arthritis, and an increased risk of lymphoma. This review synthesizes the recent findings to provide extensive updates on the disease's pathogenesis, diagnosis, and treatment. Current evidence shows that epithelial cell activation and type I interferon responses are major in initiating immune disorders. Adaptive immune systems contribute further through autoreactive B and T cells, resulting in persistent inflammation and antibody production. Diagnostic strategies have developed with the implementation of ACR/EULAR classification criteria and using both traditional (anti-SSA/Ro, anti-SSB/La) and novel biomarkers. Advances in imaging techniques, such as salivary gland ultrasound, are improving diagnostic accuracy, especially in seronegative patients. Treatment remains largely symptomatic, but B-cells are subject to activation factors, JAK-STAT pathways, and biological therapy targeting CD40-CD40L interactions in clinical trials. Despite these developments, challenges remain in early detection, treatment standardization, and systemic manifestations. This review highlights the emerging clinical and therapeutic strategies that can lead to personal care approaches and better patient results, emphasizing the need for ongoing research to close the current gap in clinical management.